Improving the fire-extinguishing effect of pneumatic extinguishers with airflow-spray synergistic jet: Investigation of nozzle position and number of nozzles - Fanbao Chen; Bin Yao; Guoqing Zhu; Wanhai Guo; Tingting Xu; Tao Deng; Zhenhua Jiang; Ziyang Wang; Min Peng; Xinyu Wang (Case Studies in Thermal Engineering, 2023)
The fire-extinguishing capability of the overheating 6 MF-30 pneumatic fire extinguisher needs to be improved. To enhance its fire-extinguishing capability, this study proposes a method of adding water through nozzles. The study conducted flow-field simulations to determine the appropriate nozzle position and replicate the synergistic jet effects using varying number of nozzles. Experimental studies were carried out to validate the simulation and demonstrate the efficiency of the synergistic jet in extinguishing fires directly. The findings show that placing the nozzle at the air duct outlet and using a higher number of nozzles is more efficient. Additionally, the synergistic jet has a better fire-extinguishing performance than pure airflow because of the cooling effects resulting from the water mist and collaborative action observed during the experimental studies. This research has significant implications for improving the efficiency and effectiveness of pneumatic fire extinguishers while advancing fire-extinguishing technology and firefighting technology.